A new species of Cephalodasys (Gastrotricha, Macrodasyida) from the Caribbean Sea with a determination key to species of the genus - Kieneke, Alexander; Schmidt-Rhaesa, Andreas; Hochberg, Rick (Zootaxa, 2015)
A new marine gastrotrich species of the genus Cephalodasys is described from shallow sublittoral coralline sand sampled between Lee Stocking Island and Norman’s Pond Cay (Exuma Cays), Bahamas. Cephalodasys interinsularis n. sp. reaches a body length of 471 µm and is characterized by a new combination of characters including six total anterior adhesive tubes and five pairs of ventrolateral adhesive tubes. The new species is morphologically similar to C. swedmarki but can be distinguished by the different number of anterior adhesive tubes, the spatial arrangement of the ventrolateral adhesive tubes, and a shorter pharynx. We provide an updated diagnosis of the genus and a determination key to all known species of Cephalodasys. C. interinsularis n. sp. is the third known species of Cephalodasys from the Caribbean marine province.